THE CHOICE OF EXCHANGE RATE SYSTEMS, ACCOUNTABILITY IMPLICATIONS, AND ECONOMIC EFFICIENCY: EMPIRICAL EVIDENCE FROM DEVELOPING COUNTRIES - Arbana Sahiti Ramushi; Shqipdona Hashani Siqani (Baltic Journal of Economic Studies, 2025)
The choice of exchange rate regimes over the period 2000-2024 has been a key policy issue for developing countries. This paper will investigate the impact of different types of exchange rate regimes – fixed, intermediate and flexible – on economic growth performance. According to empirical data collected by the International Monetary Fund and the World Bank, the results are that there is no statistically significant relationship between the choice of exchange rate regime and the level of long-term economic growth. Descriptive data, on the other hand, show that countries that have followed intermediate regimes have experienced higher growth rates compared to fixed or flexible regimes. In this regard, central accountability implications arise: the way in which economic decision-makers report, explain and coordinate exchange rate policy is directly related to the perception of institutional credibility and the effectiveness of monetary and fiscal policies. Additionally, this study highlights the importance of accurate financial reporting and transparent accounting as essential elements for strengthening institutional accountability and creating a stable economic environment in developing countries. The findings show that the effects of exchange rates on economic development are not self-governing, but interdependent with other aspects such as trade openness, investment levels and institutional stability. Therefore, transparency and accountability in the design and implementation of monetary policies are key elements for the sustainable development of developing countries.